Penggunaan Laboratorium Maya dalam Pembelajaran IPA di Sekolah Menengah Pertama di Kabupaten Tangerang - Gustomi; Elin Driana; Ernawati (Postgraduate, University of Mataram, 2025)
Virtual laboratories are seen as a promising solution to the shortcomings of conventional laboratories. This study aims to explore the use of virtual laboratory for science practicum in junior high schools, the supporting factors, the hindering factors, and perceptions of teachers and students regarding virtual laboratories. A survey were administered to five teachers and 122 students from public and private schools in Tangerang Regency. Additionally, semi-structured interviews were conducted with five teachers and 10 students who had prior experience using virtual laboratories in their learning. Quantitative data was analyzed using descriptive statistics, while qualitative data was examined through an interactive model approach. The findings reveal that virtual laboratories have been utilized by both teachers and students for laboratory activities, particularly in physics, although the usage remains infrequent. Factors such as device availability, internet connectivity, data limitations, and facility access were found to influence the extent of virtual laboratory adoption. Overall, both teachers and students perceived virtual laboratories as highly beneficial, especially for schools lacking sufficient conventional laboratory resources.